Allenes and Derivatives in Gold(I)- and Platinum(II)-Catalyzed Formal Cycloadditions - Mascareñas, José L. (Acc Chem Res, 2019)
[Image: see text] Cycloaddition reactions, by involving the formation of at least two bonds and one cycle in a single operation, represent one of the more practical ways to assemble carbo- and heterocyclic structures from simple acyclic precursors. Especially appealing are formal cycloadditions promoted by transition metals, owing to the ability of these reagents to open mechanisms that are not accessible using classical chemistry. Therefore, along the years, a great variety of annulations based on first-, and particularly second-row transition metals have been discovered. Most of these reactions involve inner sphere mechanisms, with the metal participating via standard oxidative addition or reductive elimination processes. Curiously, metals of the third row like platinum and, especially, gold remained largely unexplored, likely because of the belief that they were inert and expensive. However, from the beginning of this century, many groups realized that these metals can open very interesting mechanistic scenarios and promote novel types of transformations. In particular, the π-acidic, carbophilic behavior of gold(I) complexes, together with the possibility of tuning their reactivity using designed ligands, has triggered important activity in the field. Many gold-catalyzed transformations involved addition or cycloisomerization processes, but during recent years, there have been also important advances in the development of formal cycloaddition reactions. While many of these reactions rely on the activation of alkynes, there has been an increasing number of reports that exploit the peculiar reactivities of allenes and derivatives. In this Account, we present recent efforts on the development of platinum- and gold-catalyzed formal cycloadditions of allenes. For the sake of simplicity, we only include annulations initiated by a direct metal-promoted activation of the allene moiety. Thus, alternative Pt- or Au-catalyzed reactions wherein the allene does not interact with the metal catalyst are not covered. Upon activation by the metals, allenes generate allyl-cation alkenylmetal species that can behave as 1,2- or 1,3-carbon dipoles in cycloaddition processes. Especially relevant is the reactivity of allenamides. The presence of the amide substituent provides for the generation of gold intermediates with a good balance of reactivity and stability, which can therefore react with the corresponding partners in a controlled manner. Moreover, despite the difficulties associated with the transfer of stereochemical information from chiral linear gold(I) complexes, a variety of enantioselective gold-catalyzed annulations have been discovered. This Account is organized considering the number of atoms engaged in the annulation process, and when possible, we present the results in a chronological order.